PENGEMBANGAN E-BOOK JELAJAH LINGKUNGAN BLITAR (JELITA) PADA MATERI EKOSISTEM KELAS V SEKOLAH DASAR - Adhari, Febi; Putri Rarasati, Ida; Putriani, Ida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning (IPAS) in elementary schools requires teaching materials that are able to present the surrounding environment as a contextual and meaningful source of learning. Preliminary analysis at three elementary schools in Blitar Regency showed that teachers still rely on worksheets, pictures, and separate YouTube videos that are not fully relevant to the ecosystem topic, so that student engagement and daily test scores remain low. This study aimed to determine the feasibility and practicality of the E-book Jelajah Lingkungan Blitar (JELITA), a digital teaching material that integrates local tourism potential of Blitar Regency into ecosystem content for fifth-grade students. The study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop) developed by Thiagarajan, limited to the development stage. The product was validated by nine experts (three media, three material, and three language validators) and tried out on three certified teachers and 23 fifth-grade students of UPT SD Negeri Plosorejo 1 using a purposive sampling technique. Data were collected through validation and trial questionnaires and analyzed descriptively using a percentage formula. The results showed that the media, material, and language validation obtained percentages of 87.25% (very feasible), 75.33% (feasible), and 90.5% (very feasible) respectively. The trial results showed that the teacher and student response percentages were 94% and 83.2%, both in the very practical category. It can be concluded that the JELITA e-book is feasible and practical to be used as a contextual digital teaching material for ecosystem topics in elementary schools